Knowledge About Past and Present Financial Crises in Relation to Financial Education - Csiszárik-Kocsir, Ágnes; Varga, János; Garai-Fodor, Mónika (Public Finance Quarterly, 2021)
The crises of the past provide us aplenty of additional information to the understand the crises of the present. The crises in the past and the present have gone through very typical developmental phases in terms of their unfolding, which has already been highlighted in several studies. For this reason, it is important to know their development and operation, thus reducing the probability of future crises. It is also important to be able to distinguish the bubble from the crisis, which only occurs when the bubble bursts. However, when this happens, the effects directly or indirectly reach everyone. The level and the development of financial literacy has been a challenge not only in Hungary but also worldwide for many years. In this process, we try to understand the financial markets and to describe the tools, but how important is to discussing previous crises? In this study, we try to shed light on the knowledge of past and present crises and the related circumstances, paying a close attention on their effects in a connection of the previous financial studies with the results of a questionnaire survey conducted in 2020, basing it on extensive literature research. Our goal is to show the shortcomings of financial education, what is so important in identifying and managing crisis areas that are constantly present in the economy.